Cns Findings in Chronic Fatigue Syndrome and a Neuropathological Case Report. (August 2017) - Ferrero, Kimberly; Silver, Mitchell; Cocchetto, Alan; Masliah, Eliezer; Langford, Dianne
Chronic fatigue syndrome (CFS) is characterized as a persistent, debilitating complex disorder of unknown etiology, whereby patients suffer from extreme fatigue, which often presents with symptoms that include chronic pain, depression, weakness, mood disturbances, and neuropsychological impairment. In this mini review and case report, we address central nervous system (CNS) involvement of CFS and present neuropathological autopsy findings from a patient who died with a prior diagnosis of CFS. Among the most remarkable pathological features of the case are focal areas of white matter loss, neurite beading, and neuritic pathology of axons in the white matter with axonal spheroids. Atypical neurons displaying aberrant sprouting processes in response to injury are observed throughout cortical gray and white matter. Abundant amyloid deposits identical to AD plaques with accompanying intracellular granular structures are observed as well. Neurofibrillary tangles are also present in the white matter of the frontal cortex, thalamus and basal ganglia. Taken together, these neuropathological findings warrant further studies into CNS disease associated with CFS.